2021
DOI: 10.4103/ijo.ijo_1721_21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of online classes and home confinement on myopia progression in children during COVID-19 pandemic: Digital eye strain among kids (DESK) study 4

Abstract: Purpose: This study was performed to compare the rate of progression of myopia before and during the COVID-19 pandemic and to assess the risk factors of hastened progression. Methods: All children with myopia of spherical equivalence ≤ −0.5 D with at least two prior documented refractions 6 months and 1 year before were included. The annual progression rate before COVID-19 and during COVID-19 was calculated. Annual myopia progression was categorized as no progression (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 19 publications
1
62
0
1
Order By: Relevance
“…Several previous studies have reported on myopic progression in children and adolescents during the COVID-19 pandemic. [15][16][17] However, no evidence regarding adult myopia progression has been collected during the same period. Therefore, this study aimed to evaluate the outbreak of COVID-19-related myopia progression in early adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have reported on myopic progression in children and adolescents during the COVID-19 pandemic. [15][16][17] However, no evidence regarding adult myopia progression has been collected during the same period. Therefore, this study aimed to evaluate the outbreak of COVID-19-related myopia progression in early adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the main ocular effects observed were refractive errors (myopia), accommodation disturbances (esotropia) and visual symptoms (dry eye and fatigue) (table 1). Among the studies, 16 were conducted in Asia, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] 2 in Europe 29 30 and 3 in America. 31 32 The risk of bias assessment revealed that all of the cross-sectional studies and case series had a low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…In India, complete lockdown started at the end of March 2020 and resulted in the confinement of school-going children from April to October 2020. Mohan et al compared the rate of progression of myopia pre and during the COVID-19 pandemic in a study involving 133 children aged 6–18 [ 21 ]. The group found that 62.4% of children showed progression during the pandemic as compared with 45.9% prior to it.…”
Section: Worldwide Impact Of Covid-19 On Myopiamentioning
confidence: 99%
“…The study by Liu et al showed that lighting conditions were associated with symptoms of myopic progression [ 16 ]. However, most of these behavioral investigations were dependent on self-reporting [ 16 , 21 , 23 ], which may have introduced response bias. Ideally, a more objective method should be used for these measurements.…”
Section: Preventive Strategiesmentioning
confidence: 99%